2018
DOI: 10.1002/srin.201700515
|View full text |Cite
|
Sign up to set email alerts
|

Strain Aging Behavior of an Austenitic High‐Mn Steel

Abstract: The bake hardening treatment shows great potential for increasing the yield strength of steel components for automotive applications. This study investigates the effects of bake hardening on the yield strength and ductility of an austenitic high‐Mn steel. In order to identify a promising process window, the prestrain, the bake hardening temperature, and the annealing time are varied. The bake hardening effect is evaluated by the uniaxial tensile tests with digital image correlation (DIC) in situ monitoring. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…[20,60,61] Other investigations even show that not only does a higher pre-deformation intensifies strain aging, but also an increase in temperature or a higher strain rate during pre-deformation further accelerates the static strain aging process. [40,48] Even though our results show a correlation between C-Mn ordering and strength increase during static strain aging, this cannot be equally assumed for dynamic strain aging. This important aspect becomes apparent in the comparison of strain localization.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…[20,60,61] Other investigations even show that not only does a higher pre-deformation intensifies strain aging, but also an increase in temperature or a higher strain rate during pre-deformation further accelerates the static strain aging process. [40,48] Even though our results show a correlation between C-Mn ordering and strength increase during static strain aging, this cannot be equally assumed for dynamic strain aging. This important aspect becomes apparent in the comparison of strain localization.…”
Section: Discussionmentioning
confidence: 57%
“…The increase in YS, as known from other high-manganese steels, occurs due to strain aging. [40,48] The increase in YS is repeatedly attributed to the hindrance of the dislocation movement or a combined effect of ordering and dislocation hindering. [49][50][51] We found that the strength increase intensifies with longer aging times and higher pre-deformation (Figure 2b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ab-initio based study combined with SANS experiments by Song et al [42] and SANS experimental study by Kang et al proved the presence of Mn-C octahedral clusters and their evolution, indicating the occurrence of DSA during deformation in high Mn steels. The occurrence of static strain aging due to the presence of Mn-C SRO was stated to be responsible for increased yield strength and pronounced yielding of annealed TWIP steel [43]. It was stated that deformation twinning in TWIP steels is promoted by thermally activated nature of dislocation slip due to dynamic interactions between solute C atoms and dislocations that inhibit dislocation slip due to lattice friction effects [44].…”
Section: Strain Hardening and Twinning Evolutionmentioning
confidence: 99%
“…In the past decade, much more attention has been taken into high-manganese twinning-induced plasticity (TWIP) steels for their outstanding product of strength and plasticity, excellent energy absorption capability, impact toughness, and good formability. [1][2][3][4] The excellent properties were ascribed to unique twinning behavior during plastic deformation as well as the interaction between gliding and twinning activated with a low to medium stacking faults energy (SFE) ranging from 18 to 45 mJ m À2 . [5][6][7] These favorable mechanical properties will find important applications in a variety of engineering fields such as transportation, aerospace, and defense, where high plasticity and high impacting energy absorption capability are required.…”
Section: Introductionmentioning
confidence: 99%